4-aminopyridine - the new old drug for the treatment of neurodegenerative diseases - Ivanka Kostadinova; Nikolai Danchev (Pensoft Publishers, 2019)
In this review are described the preclinical and clinical pharmacological data as well as new therapeutic indications for the use of 4-aminopyridine. 4-aminopyridine is a potassium (K+) channel blocker that has a long history and various application areas. It is a chemical agent developed in 1963 as a bird poison. The first approval for clinical application of 4-aminopyridine was in 70's in Bulgaria, since anesthetists in that country have confirmed its effect as reversal agent for nondepolarizing myorelaxants. The Bulgarian pharmaceutical company Sopharma commersialized 4-aminopyridine under the trade name Pymadin. Since then 4-aminopyridine was extensively studied and in 2010 is approved in the USA for the treatment of walking disabilities in patients with multiple sclerosis. In recent years, data from clinical trials indicated that K-channel blockade may prove to be an appropriate strategy to overcome disturbances in nerve impulses conduction associated with demyelination of the central nervous system.